STUDY OF THE ATTENUATION EFFICIENCY OF (AISI-316) ALLOY MODIFIED WITH ALUMINUM IN THE PRESENCE OF SAMARIUM OXIDE DIFFUSION BARRIER (American Journal of Interdisciplinary Research and Development, 2022)
The research includes the preparation of alumina coatings by cementing pack on the surface of an alloy (AISI-316) grafted with a thin layer of samarium oxide barrier diffusion. The base alloy included the metallurgical variables and mechanical surface coefficients, and finding the coefficients of linear attenuation (μ_l), and mass (μ_m), for the alloy, where the surface properties of the alloy were modified by cementing it for four different times (2-4-6-8). hour, per coating. Then study the attenuation coefficients and compare them with the theoretical and practical results of the improved alloy without the coating process, and to find out the suitability of these materials for use in the field of gamma ray radiation attenuation. These atomic parameters were measured using a source (Cs-137) emitting gamma rays with a capacity of (662 keV) and an efficiency (400 KBq), and a source (Am-241) emitting a gamma ray of energy (60 keV) and an efficiency of (74 KBq). Sodium iodide detector NaI(Tl) with dimensions (〖1.5〗^"×〖1.5〗^") with integrated measurement system. The radiation dose rate was also calculated using linear attenuation coefficients. The results showed that the values of these coefficients are affected by the change in the coating time and type. It was found that when the coating time for the samples increased, the attenuation coefficients increased. The best results were obtained for samples coated at a time of 8 hours and in the presence of samarium oxide barrier, where there is a good agreement between the obtained values compared with the results of (ICUR), as the extent of difference between these results is less than 3%. The best results obtained for the uncoated sample, where there is a good agreement between the obtained values in comparison with the results of (ICUR), as the extent of difference between these results reaches 12%.